The paths of democratic construction in Algeria and their impact on the effectiveness of the political system (قضايا سياسية, 2025)
The move towards adopting the democratic principle in political organization requires the availability of a set of political foundations linked to its cultural frameworks that enhance its activities through which society interacts with its political reality, and then formulates its vision and requirements in light of the participation that grows with the response it receives from the political organization. Therefore, the mature political process is not based on foundations and institutions that lack a function and a balanced role within the system of political interaction or that are devoid of democratic practice. Therefore, what is noted about the political system in Algeria is that it has produced a tight political and organizational situation in favor of the position of the President of the Republic, reinforced by the constitutional document that placed him in an exceptional position from the balance of powers, as his decision is effective on various state institutions. The practice has also granted more monopoly of powers and the acquisition of their privileges, which has become one of the sources of its political legitimacy that has absent the peaceful transfer of power, as well as the inactivity of civil social organizations and their parties from practicing their activities in influencing the outputs of power or participating in the political decision, which justifies their existence as part of completing the form of the system, not being one of the means of political participation or a source for developing political capabilities and sustaining their activities that maintain On the stability of the system and its effectiveness, the research was devoted to identifying the sources of imbalance in the political organization of Algeria and developing effective solutions to address the reality and increase the outcomes of political performance.